Oral Challenge with Wild-Type Salmonella Typhi Induces Distinct Changes in B Cell Subsets in Individuals Who Develop Typhoid Disease. - Franklin R Toapanta; Paula J Bernal; Stephanie Fresnay; Laurence S Magder; Thomas C Darton; Claire Jones; Claire S Waddington; Christoph J Blohmke; Brian Angus; Myron M Levine; Andrew J Pollard; Marcelo B Sztein (PLoS Neglected Tropical Diseases)
A novel human oral challenge model with wild-type Salmonella Typhi (S. Typhi) was recently established by the Oxford Vaccine Group. In this model, 104 CFU of Salmonella resulted in 65% of participants developing typhoid fever (referred here as typhoid diagnosis -TD-) 6-9 days post-challenge. TD was diagnosed in participants meeting clinical (oral temperature ≥38°C for ≥12h) and/or microbiological (S. Typhi bacteremia) endpoints. Changes in B cell subpopulations following S. Typhi challenge remain undefined. To address this issue, a subset of volunteers (6 TD and 4 who did not develop TD -NoTD-) was evaluated. Notable changes included reduction in the frequency of B cells (cells/ml) of TD volunteers during disease days and increase in plasmablasts (PB) during the recovery phase (>day 14). Additionally, a portion of PB of TD volunteers showed a significant increase in activation (CD40, CD21) and gut homing (integrin α4β7) molecules. Furthermore, all BM subsets of TD volunteers showed changes induced by S. Typhi infections such as a decrease in CD21 in switched memory (Sm) CD27+ and Sm CD27- cells as well as upregulation of CD40 in unswitched memory (Um) and Naïve cells. Furthermore, changes in the signaling profile of some BM subsets were identified after S. Typhi-LPS stimulation around time of disease. Notably, naïve cells of TD (compared to NoTD) volunteers showed a higher percentage of cells phosphorylating Akt suggesting enhanced survival of these cells. Interestingly, most these changes were temporally associated with disease onset. This is the first study to describe differences in B cell subsets directly related to clinical outcome following oral challenge with wild-type S. Typhi in humans.